Low-Paid Workers and On-the-Job Training in Canada - Zeytinoglu, Isik; Cooke, Gordon; Harry, Karlene; Chowhan, James (Relations industrielles / Industrial Relations, 2008)
This paper provides evidence of on-the-job training for low-paid workers in Canada and examines workplace and individual factors associated with their on-the-job training. The study uses Statistics Canada’s Workplace and Employee Survey (WES) 2001 data. Results show that less than a quarter of low-paid workers received on-the-job training in 2001 as compared to one third of higher-paid workers. A decomposition of regression models indicated that this substantive gap is statistically significant. With the shrinking labour force, ongoing skills development is needed to enable workers to earn a decent living, fulfill their work-related goals, and contribute to the current and future productivity of their workplaces and the economy. We recommend governments provide support for low-paid workers’ on-the-job training.